EFFECT OF OLMESARTAN AND LABETALOL ON OXIDATIVE STRESS AND ANTIOXIDANT STATUS IN SOUTH INDIAN HYPERTENSIVE PATIENTS - Kodati, Devender; Lingabathula, Harikiran; Yellu, Narsimha Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: To evaluate the glutathione (GSH), lipid peroxidation, total antioxidant status levels (TAS), and liver function parameters such as serum aspartate transaminase (AST) and serum alanine transaminase (ALT) in South Indian hypertensive patients before and after olmesartan and labetalol treatment. Methods: Total 69 subjects were selected for the study. Out of 69 subjects, 29 were healthy volunteers (HVs) and 40 subjects were hypertensive patients. The patients both male and female within the age group of 20-65 years were selected. GSH, lipid peroxidation, TAS, AST, and ALT levels in serum were estimated using reported methods. Individual methods were standardized, standard graphs were plotted, and the parameters were measured. Results: Significantly fewer levels of GSH and TAS and more levels of malondialdehyde were observed in untreated hypertensive patients as compared with HVs. After drug treatment, there was significant raise in the levels of GSH and TAS as compared with untreated patients. No significant changes in AST and ALT were observed in both olmesartan and labetalol group as compared with HVs. Conclusions: The antioxidant supplementation is warranted to protect from oxidative stress attack, and the drugs such as olmesartan and labetalol were showing the significant protection against oxidative stress which can significantly reduce blood pressure and prevent possible complications in hypertensive patients. Keywords: Hypertension, Oxidative stress, Olmesartan, Labetalol, Antioxidant.